Modeling ubiquitous language learning environment / Zurainee Mohd Tahir - Mohd Tahir, Zurainee (2014)
Ubiquitous learning is a popular option amongst students and educators. The landscape of learning environments, however, has become blurry with the fusion of technology. Various studies have investigated ubiquitous learning towards multiple aspects. Most of these researches mainly focus on the study of ubiquitous learning environment. However, only little effort has touched on the configuration and elements of ubiquitous learning that focusing on language learning. Therefore, the research is carried out in Academic Language Studies to address the benefit of ubiquitous learning environment that focusing on language learning. Thus, this study create a better platform of identifying the elements that needed for ubiquitous learning environment that focusing on language learning. This thesis proposes a conceptual model for Ubiquitous Language Learning Environment (ULLE). It begins by briefly describing the definition and comparison of characteristics in ubiquitous learning followed by proposing the conceptual model of ULLE. ULLE is an integrated learning environment that combines technical, physical, informational and social settings. ULLE ensures more effective and efficient integration amongst school, home and surrounding environment. The essential elements of this model are the integration and coordination of language school, home and other places where learning can take place anywhere and anytime. The type of interaction in ULLE consists of three main subjects such as the people, the objects in the real world and the artifacts in virtual space. On technology perspectives, ULLE integrating multiple types of ubiquitous devices that using wireless communication as a tool. With the implementation of ULLE, anyone could benefit the access to the right language learning knowledge anywhere and anytime using any device at their own convenience. In order for verifying the effectiveness of the ULLE, five lecturers in Academic Language Studies, Universiti Teknologi Mara (UiTM), Shah Alam, Malaysia participated in an interview session over a period of three weeks. From the qualitative data of this research, all key informants agreed that ULLE can be a great medium and tools in facilitating the language learning. For the communication and interaction in ULLE, the integration of the model into academic learning will further enhance interaction and communication between educators and learners. With the usage of ULLE into academic learning, it will increase vocabulary acquisition, sentences and expressions of the learners. The result that obtain from this research will assist another researcher in developing ubiquitous language learning applications.